Implementing industry 4.0 in Australia: Insights from advanced Australian manufacturers - Claire M. Mason; Melanie Ayre; Shanae M. Burns (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study explores Industry 4.0 in the Australian context, where manufacturing is dominated by smaller firms servicing the domestic market. We interviewed 20 advanced Australian manufacturers from diverse fields, capturing detailed descriptions of the Industry 4.0 implementation process. We compared the themes that emerged from their descriptions with the factors typically assessed in Industry 4.0 frameworks to draw out differences in emphasis. Consistent with these frameworks, Australian manufacturers were focused on using Industry 4.0 technologies to automate the capture, integration and analysis of data. To enable this activity, they were reorganising workforce roles and developing new skill sets. Knowledge sharing and collaborations within and across the organisation were seen to be especially important for small Australian manufacturers (with limited funding for technology investment and research and development) to maintain global competitiveness. However, while most Industry 4.0 frameworks describe supply chain applications, the development of smart products and services, and the need to adopt a strategy-led approach, relatively few participants spoke about these opportunities. Even fewer addressed the need for improved governance, standards and data security in the context of Industry 4.0. We argue that these gaps are best addressed through government policy and investment focusing beyond manufacturers, to support Industry 4.0 uplift across key domestic supply chains.
Keywords: 650; Industry 4.0; digital manufacturing; Australian manufacturing; smart factory; advancedmanufacturing; manufacturing innovation